2021
DOI: 10.3390/su13052726
|View full text |Cite
|
Sign up to set email alerts
|

A Portfolio of Effective Water and Soil Conservation Practices for Arable Production Systems in Europe and North Africa

Abstract: To secure sustainable food production for meeting the growing global demand for food, it is imperative, while at the same time challenging, to make efficient use of natural resources with minimal impact on the environment. The study objective is to provide insights into the multiple benefits and trade-offs of different sustainable agricultural practices that are relevant across pedo-climatic zones in Europe and North Africa, including conservation agriculture, crop diversification, organic agriculture, and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Accordingly, implementing inspection campaigns that monitor the compliance of famers with wastewater legislation, and apply penalties to violators, is critical for enhancing the adoption by farmers of wastewater use in irrigation. In general, the adoption of SWM practices can be stimulated when farmers discover the advantages and disadvantages of different practices and have the opportunity to experiment on their own land [72].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, implementing inspection campaigns that monitor the compliance of famers with wastewater legislation, and apply penalties to violators, is critical for enhancing the adoption by farmers of wastewater use in irrigation. In general, the adoption of SWM practices can be stimulated when farmers discover the advantages and disadvantages of different practices and have the opportunity to experiment on their own land [72].…”
Section: Discussionmentioning
confidence: 99%
“…Bertol et al (2017) found that nutrient and organic carbon concentrations in run‐off from no till were higher than from conventional tillage, with the cost of erosion losses from no till being 29% higher in terms of phosphate fertilizer. These differences demonstrate potential trade‐offs and highlight how the effectiveness of soil conservation practices may vary considerably across different landscapes due to factors such as soil or crop type (Choden & Ghaley, 2021; Deasy et al, 2009). Although changing agricultural practices may be part of the solution, mitigating soil loss and diffuse pollution may require additional interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of the use of chemicals and tillage in conventional agricultural production systems has negative effects on soil health and the environment [5]. To ensure a positive economic and environmental advantage to soil ecosystems, good and effective management practices such as crop rotation, low tillage, and the planting of cover crops are very necessary [6].…”
Section: Introductionmentioning
confidence: 99%